Rio 2016 Olympic performance assessment - A European perspective - Glad, B.; Locatelli, E.; Apostolopoulos, N. (New Studies in Athletics, 2016)
The medal table for the athletics events at the 2016 Olympic Games shows that for the first time ever Europe was not the strongest of the IAAF's six Area groups. As top performances have become more globalised in the last 30 years, the percentage of medals taken by Europe has decreased, especially since 2004. This trend has been reinforced by the nullification of many performances in the last decade after re-testing of stored doping control samples and retroactive suspensions. This article examines the performances of Europe's athletes in Rio set against the context of the major events of the last two Olympic cycles. It includes short evaluations of all the competitions in Rio by an experienced head coach, statistical analysis of the medal and finalist points tables and the Performance Delivery Index (PDI), which quantifies success at meeting basic objectives for a major championships. The authors suggest that Europeans responsible for high-performance results should consider all factors impacting major event success, learn from countries in other parts of the world that are taking a greater percentage of medals than in the past and use the PDI as a measure of incremental improvements.